The effect of feeding inorganic and organic selenium sources on the performance and content of selenium in milk of transition dairy cows - Khalili, Mohsen; Chamani, Mohammad; Amanlou, Hamid; Nikkhah, Ali; Sadeghi, Aliasghar (Acta Scientiarum. Animal Sciences, 2019)
The aim of this study was to determine the effects of supplementing close-up and fresh dairy cows’ diets with sodium selenite or organic sources of selenium (Se) on the dry matter intake (DMI), milk production and composition. Based on their body condition score (BCS), previous lactation milk yield and expected calving date, 24 multiparous Holstein dairy cows were balanced and randomly assigned to 4 experimental treatments. Experimental treatments were: control (basal diet without Se supplementation with 0.10 and 0.15 mg of Se kg-1 DM in close-up and fresh diets, respectively), sodium selenite supplementation (0.50 mg of Se kg-1 DM; Se-S), selenium yeast supplementation (0.50 mg of Se kg-1 DM; Se-Y) and selenomethionine supplementation (0.50 mg of Se kg-1 DM; Se-M). Neither Se supplementation nor Se source affected DMI pre- and postpartum. Milk production and composition were not different across Se sources, but concentrations of Se in milk were 14 and 10% greater for cows fed Se-M and Se-Y than for those fed control, respectively. Cows fed Se–M had lower somatic cell count than control (SCC; 173.11 vs. 318.89 cells × 103 Ml-1). The changes of BW and BCS pre- and postpartum were not affected by treatments over experimental period. The results of present study showed that selenomethionine supplementation compared to other sources decreased SCC in transition cows. In addition, milk Se concentrations increased in Se-Y and Se-M groups more significantly compared to the Se-S group. This indicates that organic Se had better replace inorganic Se for transition dairy cows.